Variability and limits of nitrogen and phosphorus resorption during foliar senescence - Estiarte, Marc; Campioli, Matteo; Mayol, Maria; Penuelas, Josep (Plant communications, 2023)
Foliar nutrient resorption (NuR) plays a key role in ecosystem functioning and plant nutrient economy. Most of this recycling occurs during the senescence of leaves and is actively addressed by cells. Here, we discuss the importance of cell biochemistry, physiology, and subcellular anatomy to condition the outcome of NuR at the cellular level and to explain the existence of limits to NuR. Nutrients are transferred from the leaf in simple metabolites that can be loaded into the phloem. Proteolysis is the main mechanism for mobilization of N, whereas P mobilization requires the involvement of different catabolic pathways, making the dynamics of P in leaves more variable than those of N before, during, and after foliar senescence. The biochemistry and fate of organelles during senescence impose constraints that limit NuR. The efficiency of NuR decreases, especially in evergreen species, as soil fertility increases, which is attributed to the relative costs of nutrient acquisition from soil decreasing with increasing soil nutrient availability, while the energetic costs of NuR from senescing leaves remain constant. NuR is genetically determined, with substantial interspecific variability, and is environmentally regulated in space and time, with nutrient availability being a key driver of intraspecific variability in NuR. Foliar nutrient resorption (NuR) plays a key role in ecosystem functioning and plant nutrient economy. Most of this recycling occurs during leaf senescence and is actively addressed by cells. This review discusses the importance of cell biochemistry, physiology, and subcellular anatomy to condition the outcome of NuR at the cellular level and to explain the existence of limits to NuR. NuR is genetically determined, with substantial interspecific variability, and is environmentally regulated in space and time, with nutrient availability being a key driver of intraspecific variability in NuR.